2003
DOI: 10.1074/jbc.m309759200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of Fatty Acid Transport Protein-4 Results in Early Embryonic Lethality

Abstract: Fatty acid transport protein-4 (FATP4) is the major FATP in the small intestine. We previously demonstrated, using in vitro antisense experiments, that FATP4 is required for fatty acid uptake into intestinal epithelial cells. To further examine the physiological role of FATP4, mice carrying a targeted deletion of FATP4 were generated. Deletion of one allele of FATP4 resulted in 48% reduction of FATP4 protein levels and a 40% reduction of fatty acid uptake by isolated enterocytes. However, loss of one FATP4 all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 39 publications
(45 reference statements)
4
92
1
2
Order By: Relevance
“…The fact that a positive relationship exists between FATP-4 protein and LCFA uptake by enterocytes in FATP4 1/2 mice is consistent with this assumption (22).…”
Section: Discussionsupporting
confidence: 75%
“…The fact that a positive relationship exists between FATP-4 protein and LCFA uptake by enterocytes in FATP4 1/2 mice is consistent with this assumption (22).…”
Section: Discussionsupporting
confidence: 75%
“…More recently, blocking of FATP4 function has been targeted as an alternative treatment to pancreatic lipase inhibitors for inhibition of fat absorption. Using targeted deletion, Gimeno et al [38] demonstrated that the loss of one allele of FATP4 in mice reduced fatty acid uptake but did not alter fat absorption on either a normal-fat diet or a high-fat diet. Deletion of both FATP4 alleles, however, resulted in embryonic lethality.…”
Section: Gene Expressionmentioning
confidence: 99%
“…For example, ACSL6 preferentially activates very-long-chain polyunsaturated FAs, and when ACSL6 is overexpressed in PC12 neurons, it enhances the uptake and metabolism of docosahexaenoic acid relative to oleic acid [44]. In the several mouse models that lack FATP4 (Table 3), mice are variably characterized by altered epidermal FA composition accompanied by a neonatally lethal restrictive dermopathy [45], altered skin development, impaired hair growth and abnormal lipid metabolism [46], and early embryonic lethality [47]. The decreased amount of very-long-chain FAs in tissues from FATP4 knockouts supports data from ACS activity assays showing that FATP4 prefers very-long-chain FAs over long chain FAs [45].…”
Section: Role Of Acyl-coa Synthetases In Fa Channelingmentioning
confidence: 99%